Ocular findings in Baraitser–Winter syndrome with a de novo mutation in the ACTG1 gene: a case report - Jae Won Kim; Sook-Young Kim; Donghun Lee (BMC Ophthalmology)
Abstract Background Baraitser–Winter syndrome (BWS) is rare, and no previous reports have described the visual course of patients with this condition. Herein, we report the long-term visual outcomes and ocular features of a 6-year-old patient diagnosed with BWS. Case presentation A 6-year-old female patient visited our clinic complaining of low vision. External examination revealed mild ptosis and hypertelorism, and the patient had mild intellectual disability. Her visual acuity during the first visit was 20/100 in the right eye and 20/50 in the left eye. Cycloplegic refraction revealed compound hyperopic astigmatism that was more severe in the right eye than in the left eye. Anterior segment examination revealed an iris coloboma at the inferior margin in both eyes. Fundus examination revealed huge, inferior retinal colobomata in both eyes. The macular contours were normal on optical coherence tomography. Considering the ophthalmic features and systemic signs, the patient was recommended to undergo genetic evaluation. Whole-exome sequencing revealed a heterozygous, de novo, and likely pathogenic variant (c.502G > T; p.Gly168Cys) in actin gamma 1 (ACTG1), and the patient was finally diagnosed with BWS. To further evaluate her systemic abnormalities, examinations including brain imaging and laboratory tests, were performed. Brain magnetic resonance imaging revealed a congenital cortical malformation with pachygyria, and pure-tone audiometry demonstrated bilateral sensorineural hearing loss. Echocardiographic and kidney ultrasonographic features were normal. The patient’s amblyopia was treated with eye glasses for full correction and occlusion of her left eye. After 3 years of regular follow-up after the initial diagnosis, the patient’s visual acuity improved to 25/25 in both eyes. With the collaboration of pediatricians, the patient and her guardians were fully counseled on the expected symptoms and complications associated with BWS, and her long-term growth trends were being observed at the time of reporting. Conclusions BWS, a rare genetic disease, was diagnosed in a pediatric patient who presented with various ophthalmic signs, including ptosis, retinal colobomata, and iris colobomata. If the optic disc and macula are spared from the retinal coloboma, a favorable visual outcome may be achieved via consistent treatment for amblyopia and regular follow-up.